Impact of Pediococcus pentosaceus YF01 on the exercise capacity of mice through the regulation of oxidative stress and alteration of gut microbiota - Yang, Xiaoguang; Wang, Yeni; Yang, Yuhua (Frontiers in Microbiology, 2024)
Using treadmill training, this study replicated human exercise conditions and triggered exerciseinduced fatigue in mice to examine the potential of Pediococcus pentosaceus YF01 in delaying this fatigue by regulating oxidative stress and its impact on the exercise capacity and gut microbiota of mice. The exercise capacity of mice was tested by conducting exhaustion tests, determining histopathological changes in mouse tissues, detecting the levels of serum biochemical markers, and evaluating the mRNA expression levels of relevant genes. YF01 prolonged the exhaustion time of mice, increased the serum levels of oxidative stress-related markers T-AOC, CAT, and GSH, as well as GLU and LA levels in the mice. YF01 decreased the levels of hepatic-related markers AST and ALT, as well as exercise-related markers LDH, BUN, UA, and CRE in the mice. YF01 upregulated the mRNA expression of MyHc I, SIRT1, and PGC in muscle tissues, as well as SOD1, SOD2, and CAT in both liver and muscle tissues. YF01 also downregulated the mRNA expression of MyHc IIa, MyHc IIb, and MyHc IIx in muscle tissues. Furthermore, YF01 increased the abundance of beneficial bacteria such as Lactobacillus and Lachnospiraceae in the gut microbiota of mice. In conclusion, P. pentosaceus YF01 may affect the exercise capacity of mice by modulating oxidative stress levels, thereby offering novel ideas for developing of sports science and human health.